Vacancy defects in Ga2O3: First-principles calculations of electronic structure - Usseinov, Abay; Koishybayeva, Zhanymgul; Platonenko, Alexander; Pankratov, Vladimir; Suchikova, Yana; Akilbekov, Abdirash; Zdorovets, Maxim; Purans, Juris; Popov, Anatoli I. (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
First-principles density functional theory (DFT) is employed to study the electronic structure of oxygen and gallium vacancies in monoclinic bulk β-Ga2 O3 crystals. Hybrid exchange– correlation functional B3LYP within the density functional theory and supercell approach were successfully used to simulate isolated point defects in β-Ga2 O3. Based on the results of our calcu-lations, we predict that an oxygen vacancy in β-Ga2 O3 is a deep donor defect which cannot be an effective source of electrons and, thus, is not responsible for n-type conductivity in β-Ga2 O3. On the other hand, all types of charge states of gallium vacancies are sufficiently deep acceptors with transition levels more than 1.5 eV above the valence band of the crystal. Due to high formation energy of above 10 eV, they cannot be considered as a source of p-type conductivity in β-Ga2 O3. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Published under the CC BY 4.0 license.
This research was funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. AP08856540) as well as by the Latvian research council via the Latvian National Research Program under the topic ?High-Energy Physics and Accelerator Technologies?, Agreement No: VPP-IZM-CERN-2020/1-0002 for A.I. Popov. In addition, J. Purans is grateful to the ERAF project 1.1.1.1/20/A/057 while A. Platonenko was supported by Latvian Research Council No. LZP-2018/1-0214. The authors thank A. Lushchik and M. Lushchik for many useful discussions. The research was (partly) performed in the Institute of Solid State Physics, University of Latvia ISSP UL. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities Union Horizon 2020, H2020-WIDESPREAD-01?2016?2017-TeamingPhase2 under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES; Deep donor; DFT; Oxygen vacancy; P-type conductivity; Point defects; β-Ga2 O3